Qualitative Assessment of a Novel Efficacy-Focused Training Intervention for Public Health Workers in Disaster Recovery. (13th April 2016) - Tower, Craig; Altman, Brian A.; Strauss-Riggs, Kandra; Iversen, Annelise; Garrity, Stephanie; Thompson, Carol B.; Walsh, Lauren; Rutkow, Lainie; Schor, Kenneth; Barnett, Daniel J.
Abstract: Objective: We trained local public health workers on disaster recovery roles and responsibilities by using a novel curriculum based on a threat and efficacy framework and a training-of-trainers approach. This study used qualitative data to assess changes in perceptions of efficacy toward Hurricane Sandy recovery and willingness to participate in future disaster recoveries. Methods: Purposive and snowball sampling were used to select trainers and trainees from participating local public health departments in jurisdictions impacted by Hurricane Sandy in October 2012. Two focus groups totaling 29 local public health workers were held in April and May of 2015. Focus group participants discussed the content and quality of the curriculum, training logistics, and their willingness to engage in future disaster recovery efforts. Results: The training curriculum improved participants' understanding of and confidence in their disaster recovery work and related roles within their agencies (self-efficacy); increased their individual- and agency-level sense of role-importance in disaster recovery (response-efficacy); and enhanced their sense of their agencies' effective functioning in disaster recovery. Participants suggested further training customization and inclusion of other recovery agencies. Conclusion: Threat- and efficacy-based disaster recovery trainings show potential to increase public health workers' sense of efficacy and willingness to participate in recovery efforts. ( Disaster Med Public Health Preparedness . 2016;10:615–622)